2010
DOI: 10.1139/p10-021
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic excitations of spin and orbital moments in cobalt oxideSpecial issue on Neutron Scattering in Canada.

Abstract: Magnetic and phonon excitations in the antiferromagnet CoO with an unquenched orbital angular momentum are studied by neutron scattering. Results of energy scans in several Brillouin zones in the (HHL) plane for energy transfers up to 16 THz are presented. The measurements were performed in the antiferromagnetic ordered state at 6 K (well below TN ∼290 K) as well as in the paramagnetic state at 450 K. Several magnetic excitation modes are identified from the dependence of their intensity on wavevector and temp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 18 publications
(18 reference statements)
4
20
0
Order By: Relevance
“…7 b,c. In both samples, two distinct peaks were observed at ≈ 20 meV and 30 meV, in reasonable agreement with previously reported spin wave energies [31][32][33][34] . Just as for the 3 meV E 1 peaks, we see that the linewidths of these higher energy magnetic excitations are substantially larger in the nanoparticle sample, although the excitation energies are only slightly shifted.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…7 b,c. In both samples, two distinct peaks were observed at ≈ 20 meV and 30 meV, in reasonable agreement with previously reported spin wave energies [31][32][33][34] . Just as for the 3 meV E 1 peaks, we see that the linewidths of these higher energy magnetic excitations are substantially larger in the nanoparticle sample, although the excitation energies are only slightly shifted.…”
Section: Discussionsupporting
confidence: 92%
“…Before we begin our discussion of the physical origin of these excitations, we will establish an explicit comparison of intensities between our experiments and previous triple axis neutron scattering studies that were carried out on CoO crystals [31][32][33][34] . These latter experiments were either carried out at much higher energy transfers than ours, or found no excitations at the low energies of our experiments, focussing instead on the magnetic excitations found at energies of 20 -30 meV and above.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16 The nature of the surface of the CoO crystal was examined with optical and scanning electron microscopy and the results showed there was only one growth domain. X-ray scattering measurements showed that the surface had a mosaic spread of about 0.1…”
Section: A Samples and Preparationmentioning
confidence: 99%